INTERNET ADDICTION AND LEVEL OF ANXIETY AMONG SCHOOL STUDENTS - D. Deep Kaur Gulati; Mamta Bakliwal (Human Research in Rehabilitation, 2023)
Internet Addiction is a rising problem among the Indian school students. The purpose of this research was to find out the extent of internet addiction among higher secondary level school students and the anxiety of higher secondary level school students having different levels of internet addiction. The research was conducted on 600 students of CBSE schools in Bhopal. The information was collected by Internet Addiction Scale and General Anxiety Scale. The findings revealed that 10% had normal level of internet addiction, 56% had mild level of internet addiction, 33% had moderate level of internet addiction and just 1% had severe level of internet addiction, the lower the level of internet addiction the lower will be the anxiety of the higher secondary level school students and girls are found to have significantly higher anxiety than boys.